Strengthening Positive Emotions in the Perspective of Islamic Education Psychology and Its Implications on Students' Enthusiasm for Learning - Aulia, Agnely Risqy; Satwika, Yohana Wuri (Ananda: Jurnal Pendidikan Anak dan Remaja, 2026)
This study aims to explore the reinforcement of positive emotions in the perspective of Islamic educational psychology and its implications for students' enthusiasm for learning. The background of this study rests on the gap between the dominant cognitive learning approach and the lack of attention to the affective and spiritual dimensions of students. This research uses a qualitative approach of case study type, with the location at SMA Negeri 1 Banguntapan Yogyakarta which has strong potential in the integration of Islamic values in learning activities. Data were obtained through participatory observation, semi-structured interviews, and documentation, then analyzed thematically. The results show that positive emotions such as gratitude, patience, and enthusiasm for learning emerge in a supportive classroom atmosphere, empathic teacher-student interactions, and routine Islamic activities at school. The role of teachers is very important in fostering positive emotions through exemplary, Islamic motivation, and the use of verses/hadith in learning. The findings show that the Islamic educational psychology approach is not only relevant but also effective in shaping students' emotional resilience and learning motivation. This research contributes to the development of a holistic education model and offers learning strategies that touch the minds, hearts and spirituality of students.